FAKTOR FAKTOR YANG MEMPENGARUHI EFISIENSI PERUSAHAAN PADA BANK PEMBANGUNAN DAERAH TAHUN 2015 - 2019 - Tiara, Silvia Agustin; Djaddang, Syahril; Mulyadi, JMV; Syailendra, Syailendra (Universitas Trilogi, 2023)
This study aims to find out and analyze whether the variables ROA, CAR, BOPO, and NPL affect the efficiency of companies at Regional Development Banks (BPD) and determine the effect of earnings quality as a moderator. The sample used in this research comes from BPD in Indonesia with audited financial statements. The population was taken from the period 2015 to 2019. The data used is secondary data using multiple linear regression analysis techniques. The results of this study indicate that the CAR and NPL variables have a significant effect on efficiency, while the ROA and BOPO variables do not have a significant effect on efficiency, the existence of Profit Quality as a moderator of the four independent variables also does not have a significant effect on BPD efficiency in Indonesia in 2015 -2019. The magnitude of the effect of the variables ROA, CAR, BOPO, NPL, and Profit Quality as a moderator has a coefficient of determination of 27.8%. In comparison, 72.2% efficiency is explained by other variables outside of this study.Keywords: Operating Expenses to Operating Income, Capital Adequacy Ratio, Profit Quality, Non Performing Loans, Return On Assets